A Comparison Of Precedence And Resistance Between Arabic And English Through Modern Science Of Linguistic - Dzulhajj Aeyn Abe Siregar (Proceeding International Seminar of Islamic Studies, 2019)
Human civilization is strongly intertwind (interdependent) with the spoken language. A pride of a nation is within its language. A nation will be honored due to its language and vice versa. As Hopkyns says (2017) “As English now occupies an important position in many education systems around the world, which is certainly the case in the Gulf Cooperate Council (GCC) states, it has become the ‘global academic lingua franca’ (Jenkins, 2014, p. 10) or ‘lingua academica’ (Phillipson, 2008) and a ‘high stakes gatekeeper of educational and social success’ (Al-Mahrooqi & Denman, 2015, p. 3)”. In post-modern world (information age) English is considered as an edicational language and leave other language as a second reference. Meanwhile at the other half of the world, Arabic nations only seen as sublatern under the influence of super-nation. Even though, as we know since 1950 middle east has become the central of liquid energy for the world, and the biggest militer-coalition is held by the Arabic-speaker nations known as Organisation of Islamic Cooperation (OIC). Historicaly speaking, the term Dark Age is correlatively connected to Golden Age in eastern term despite their contribution to the modern world.